Positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By forming a porous cladding layer on the high-nickel ternary positive electrode material, the cladding structure of Zr, Y, Mo and Mg, Na, and Sn elements is solved, and the problems of lithium ion transmission obstacles and structural instability under high voltage are solved. Improves the circulation performance and structural stability of the material.

CN119230757APending Publication Date: 2024-12-31TIANJIN B&M SCI & TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661805.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The high-nickel ternary positive electrode material has a strong side reaction with the electrolyte under high voltage conditions, which hinders the rapid transmission of lithium ions, leads to an increase in impedance, high surface residual lithium content affects the coating process, and the unstable layered structure leads to deterioration of cycling performance. .

Method used

A positive electrode material covering the porous layer structure includes a core and two cladding layers. The first cladding layer contains Zr, Y, Mo and W elements, and the second cladding layer contains Mg, Na and Sn elements, and passes through multiple times. Calcination forms a porous cladding layer to reduce surface residual lithium and structural instability.

Benefits of technology

Effectively reduce surface residual lithium, improve the deintercalation and circulation performance of lithium ions, enhance structural stability, improve electronic transmission rate and mechanical strength, and avoid direct contact between electrode materials and electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230757A_ABST
    Figure CN119230757A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, the positive electrode material comprises an inner core and a porous coating layer at least coating the surface of the inner core, and the porous coating layer comprises a first coating layer and a second coating layer which are sequentially laminated from the surface far away from the inner core. The structural stability and the cycle performance of the positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery. Background Art

[0002] High-nickel ternary positive electrode materials have the advantages of high capacity and low cost. However, in practical applications, under high voltage conditions, the side reactions between high-nickel ternary positive electrode materials and electrolytes are strong, which in turn hinders the rapid transmission of lithium ions and increases their impedance. On the other hand, the surface residual lithium content of high-nickel ternary positive electrode materials is too high, which affects the coating process of high-nickel ternary positive electrode materials and makes the preparation of electrode sheets difficult. In addition, under high-voltage working conditions, with the deintercalation of lithium ions, the layered positive electrode material becomes structurally unstable due to volume expansion, causing cracks in the active material particles and then pulverization and shedding, seriously affecting the material's cyclic stability performance. Summary of the invention

[0003] Based on this, the present application provides a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery to improve the structural stability and cycle performance of the positive electrode material.

[0004] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a core, and a porous coating layer coated on at least a portion of the surface of the core, the porous coating layer comprising a first coating layer and a second coating layer stacked in sequence in a direction away from the surface of the core;

[0005] The core comprises a chemical formula of LiNi x Co y Mn z M a O2 materials, wherein 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1;

[0006] The first coating layer comprises a chemical formula of LiNi x1 Co y1 Mn z1 M a1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1;

[0007] The second coating layer comprises a chemical formula of LiNi x2 Co y2 Mn z2 Ma2 Q1 b2 Q2 c2 O2, Q2 element includes at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1;

[0008] The M element includes at least one of Al, Ti, V and Cr.

[0009] In some embodiments, the molar ratio of the Q1 element to the Q2 element in the porous coating layer is 3.5:1 to 4.5:1.

[0010] In some embodiments, the mass content of the Q1 element in the positive electrode material is 0.001%~0.1%.

[0011] In some embodiments, the mass content of the Q2 element in the positive electrode material is 0.001%~0.2%.

[0012] In some embodiments, the mass content of the M element in the positive electrode material is 0.001% to 0.5%.

[0013] In some embodiments, the specific surface area of ​​the porous coating layer is 0.3 m 2 / g~0.7m 2 / g.

[0014] In some embodiments, the median particle size Dv50 of the positive electrode material is 9 μm to 12 μm.

[0015] In a second aspect, the present application provides a method for preparing a positive electrode material, the method for preparing a positive electrode material comprising:

[0016] The lithium source, the cathode material precursor and the compound containing the M element are mixed, and after the first calcination, a LiNi x Co y Mn z M a The core of the material of O2, wherein 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1;

[0017] The core is mixed with a compound containing an N element to obtain a mixture, and subjected to a second calcination to form a first coating layer on the surface of the core to obtain an intermediate material; the first coating layer includes a chemical formula of LiNi x1 Co y1 Mn z1 Ma1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1;

[0018] The intermediate material is mixed with a compound containing the Q2 element, and subjected to a third calcination to form a second coating layer on the surface of the intermediate material to obtain the positive electrode material, wherein the second coating layer includes a chemical formula of LiNi x2 Co y2 Mn z2 M a2 Q1 b2 Q2 c2 O2, Q2 element includes at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1;

[0019] The M element includes at least one of Al, Ti, V and Cr.

[0020] In some embodiments, the molar ratio of the positive electrode material precursor to the lithium source is 1:1.02 to 1:1.05.

[0021] In some embodiments, the compound containing the M element accounts for 0.01% to 1.00% of the total mass of the lithium source and the positive electrode material precursor.

[0022] In some embodiments, the compound containing the Q1 element accounts for 0.01% to 0.10% of the mass of the inner core.

[0023] In some embodiments, the compound containing the Q2 element accounts for 0.01% to 0.20% of the mass of the intermediate material.

[0024] In some embodiments, the first calcination is performed at a temperature of 550° C. to 650° C., for a time of 1.5 h to 3 h, in an oxygen-containing atmosphere.

[0025] In some embodiments, the second calcination comprises: sequentially performing a first stage calcination and a second stage calcination on the mixture.

[0026] Optionally, the temperature of the first stage calcination is 580° C. to 620° C., the time is 5 h to 6 h, and the atmosphere is an oxygen-containing atmosphere.

[0027] Optionally, the temperature of the second stage calcination is 750° C. to 800° C., the time is 11 h to 14 h, and the atmosphere is an oxygen-containing atmosphere.

[0028] In some embodiments, the third calcination is carried out at a temperature of 250° C. to 300° C., for a time of 4.5 h to 6 h, in an oxygen-containing atmosphere.

[0029] In a third aspect, the present application provides a positive electrode plate, comprising at least one of the positive electrode material as described in the first aspect and the positive electrode material prepared by the preparation method as described in the second aspect.

[0030] In a fourth aspect, the present application provides a secondary battery, comprising the positive electrode plate as described in the third aspect.

[0031] Compared with the traditional technology, this application has at least the following beneficial effects:

[0032] The positive electrode material of the present application forms a porous coating layer by coating Q1 element and Q2 element, which can effectively reduce the residual lithium on the surface and reduce the release of active lithium during the water washing process. Among them, the first coating layer contains Q1 element, which can also promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer contains Q2 element, which can avoid the structural change caused by the volume change of the positive electrode material during the deintercalation of lithium ions, so as to enhance the structural stability of the positive electrode material. The first coating layer and the second coating layer cooperate to improve the structural stability and cycle performance of the positive electrode material.

[0033] Furthermore, the first coating layer has a relatively high ionic conductivity, and the movement of the Q1 element between the lattices promotes the conduction of electrons to increase the electron transfer rate, which can promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer is a structural stabilization layer, which contains the Q2 element to avoid structural changes caused by volume changes of the positive electrode material during the deintercalation of lithium ions, so as to enhance the structural stability of the positive electrode material and avoid direct contact between the electrode material and the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a SEM image of the positive electrode material provided in Example 4 of the present application;

[0035] Figure 2 This is a SEM image of the positive electrode material provided in Comparative Example 1 of the present application;

[0036] Figure 3 This is a graph showing the relationship between the number of cycles and the capacity retention rate of the positive electrode material in Example 4 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0037] Below in conjunction with the embodiments and examples, the present application is further described in detail. These embodiments and examples are only used to illustrate the present application and are not used to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms, and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present application, and the equivalent form obtained also falls within the protection scope of the present application. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0039] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0040] In this application, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0041] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0042] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0043] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0044] Although high-nickel ternary positive electrode materials have a high energy density, they have a high residual lithium content on the surface. In traditional technology, the problem of residual lithium on the surface of high-nickel ternary materials is solved by wet treatment after one sintering and dry coating of additives during the preparation process of high-nickel ternary materials. However, during the process, the material inevitably comes into contact with air, thereby forming Li2CO3 that is difficult to remove. At the same time, high surface residual lithium will also lead to irreversible capacity loss and deterioration of cycle performance. In addition, under high-voltage working conditions, with the deintercalation of lithium ions, the layered positive electrode material becomes structurally unstable due to volume expansion, causing cracks in the active material particles and then pulverization and shedding, seriously affecting the cycle stability performance.

[0045] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a core, and a porous coating layer coated on at least a portion of the surface of the core, the porous coating layer comprising a first coating layer and a second coating layer stacked in sequence in a direction away from the surface of the core;

[0046] The core comprises a chemical formula of LiNix Co y Mn z M a O2 material, wherein the M element includes at least one of Al, Ti, V and Cr, 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1;

[0047] The first coating layer comprises a chemical formula of LiNi x1 Co y1 Mn z1 M a1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1;

[0048] The second coating layer comprises a chemical formula of LiNi x2 Co y2 Mn z2 M a2 Q1 b2 Q2 c2 O2, Q2 elements include at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1.

[0049] In the above embodiment, the positive electrode material forms a porous coating layer by coating the Q1 element and the Q2 element, which can effectively reduce the residual lithium on the surface and reduce the release of active lithium during the water washing process. Among them, the first coating layer contains the Q1 element, which can also promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer contains the Q2 element, which can avoid the structural changes caused by the volume change of the positive electrode material during the deintercalation of lithium ions, so as to enhance the structural stability of the positive electrode material. The first coating layer and the second coating layer cooperate to enhance the structural stability and cycle performance of the positive electrode material. Further, the first coating layer has a relatively high ionic conductivity, and the movement of the Q1 element between the lattices promotes the conduction of electrons to increase the electron transfer rate, which can promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer is a structural stabilizing layer, which contains the Q2 element to avoid the structural changes caused by the volume change of the positive electrode material during the deintercalation of lithium ions, so as to enhance the structural stability of the positive electrode material and avoid direct contact between the electrode material and the electrolyte.

[0050] It is understood that x, x1 and x2 independently include but are not limited to: 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89 or 0.90. y, y1 and y2 independently include but are not limited to: 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13 or 0.14. z, z1 and z2 independently include but are not limited to: 0.01, 0.02, 0.03, 0.04, 0.05 or 0.06. a, a1 and a2 independently include but are not limited to: 0.004, 0.008, 0.012, 0.016, 0.020, 0.024, 0.028, 0.032, 0.036 or 0.040. b1 and b2 independently include but are not limited to: 0.0002, 0.0004, 0.0006, 0.0008, 0.0010, 0.0012, 0.0014, 0.0016, 0.0018 or 0.0020. c2 includes but is not limited to: 0.00005, 0.00010, 0.00015, 0.00020, 0.00025, 0.00030, 0.00035, 0.00040, 0.00045 or 0.00050.

[0051] In some embodiments, the molar ratio of the Q1 element to the Q2 element in the porous coating layer is 3.5:1 to 4.5:1. For example, it can be 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1 or 4.5:1. The molar ratio of the Q1 element to the Q2 element in the porous coating layer is selected as above in the present application to effectively ensure the structural stability and cycle performance of the positive electrode material.

[0052] In some embodiments, the mass content of the Q1 element in the positive electrode material is 0.001%~0.1%, for example, it can be 0.001%, 0.005%, 0.010%, 0.020%, 0.030%, 0.040%, 0.050%, 0.060%, 0.070%, 0.080%, 0.090% or 0.100%.

[0053] In some embodiments, the mass content of the Q2 element in the positive electrode material is 0.001%~0.2%, for example, it can be 0.001%, 0.010%, 0.020%, 0.040%, 0.060%, 0.080%, 0.100%, 0.120%, 0.140%, 0.160%, 0.180% or 0.200%.

[0054] The present application selects the contents of Q1 element and Q2 element in the porous coating layer as above, which effectively ensures the structural stability and cycle performance of the positive electrode material.

[0055] In some embodiments, the mass content of the M element in the positive electrode material is 0.001% to 0.5%, for example, it can be 0.001%, 0.050%, 0.100%, 0.150%, 0.200%, 0.250%, 0.300%, 0.350%, 0.400%, 0.450% or 0.500%. The content of the M element is selected as above in the present application, and cooperates with the porous coating layer to effectively ensure the structural stability and cycle performance of the positive electrode material.

[0056] In some embodiments, the specific surface area of ​​the porous coating layer is 0.3 m 2 / g~0.7m 2 / g, for example, it can be 0.30m 2 / g, 0.34m 2 / g, 0.38m 2 / g, 0.42m 2 / g, 0.46m 2 / g, 0.50m 2 / g, 0.54m 2 / g, 0.58m 2 / g, 0.62m 2 / g, 0.66m 2 / g or 0.70m 2 / g. The specific surface area of ​​the porous coating layer is selected as above in the present application to effectively ensure the structural stability and cycle performance of the positive electrode material.

[0057] In some embodiments, the median particle size Dv50 of the positive electrode material is 9 μm to 12 μm, for example, it can be 9.0 μm, 9.3 μm, 9.6 μm, 9.9 μm, 10.2 μm, 10.5 μm, 10.8 μm, 11.1 μm, 11.4 μm, 11.7 μm or 12.0 μm.

[0058] A second aspect of the present application provides a method for preparing a positive electrode material, the method for preparing a positive electrode material comprising:

[0059] The lithium source, the cathode material precursor and the compound containing the M element are mixed, and after the first calcination, a LiNi x Co y Mn z M a The core of the material of O2, the M element includes at least one of Al, Ti, V and Cr, 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1;

[0060] The core is mixed with a compound containing the Q1 element to obtain a mixture, and subjected to a second calcination to form a first coating layer on the surface of the core to obtain an intermediate material; the first coating layer includes a chemical formula of LiNi x1 Co y1 Mn z1 M a1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1;

[0061] The intermediate material is mixed with a compound containing the Q2 element, and subjected to a third calcination to form a second coating layer on the surface of the intermediate material to obtain the positive electrode material, wherein the second coating layer includes a chemical formula of LiNi x2 Co y2 Mn z2 M a2 Q1 b2 Q2 c2 O2, Q2 elements include at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1.

[0062] The coating treatment added after the core material of this application is sintered once forms a uniform porous coating layer on the surface of the positive electrode material. On the one hand, it limits the contact between the surface of the positive electrode material and the air to form Li2CO3 which is difficult to decompose, effectively reduces the residual lithium content on the surface, and inhibits the disadvantage of battery gas production. On the other hand, the coating layer provides a shell protection structure for the positive electrode material, inhibits the structural changes during the lithium ion deintercalation process, and improves the cycle stability of the positive electrode material battery. Among them, the first coating layer has a relatively high ionic conductivity, and the movement of the Q1 element between the lattices promotes the conduction of electrons to increase the electron transfer rate, which can promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer is a structural stabilization layer, which contains the Q2 element to avoid the structural changes caused by the volume change of the positive electrode material during the lithium ion deintercalation process, so as to enhance the structural stability of the positive electrode material and avoid direct contact between the electrode material and the electrolyte.

[0063] In some embodiments, the molar ratio of the positive electrode material precursor to the lithium source is 1:1.02 to 1:1.05, for example, 1:1.02, 1:1.03, 1:1.04 or 1:1.05.

[0064] In some embodiments, the compound containing the M element accounts for 0.01% to 1.00% of the total mass of the lithium source and the positive electrode material precursor, for example, it can be 0.01%, 0.05%, 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90 or 1.00%.

[0065] In some embodiments, the compound containing the Q1 element accounts for 0.01% to 0.10% of the mass of the inner core, for example, it can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.10%.

[0066] The present application controls the content of the Q1 element. Therefore, in implementation, the present application selects the amount of compound addition of the Q1 element as above, which can effectively improve the thermal stability and cycle performance of the positive electrode material and optimize the performance of the battery. If the amount of compound addition containing the Q1 element is relatively high, a non-conductive phase may be formed in the porous coating layer, resulting in a decrease in the conductivity of the material and affecting the performance of the battery. In addition, if the amount of Q1 element doping is relatively high, it may also cause changes in the crystal structure of the material, generate stress, and then affect the cycle performance and mechanical stability of the material, and increase the material cost and affect the economy. If the amount of compound addition containing the Q1 element is relatively low, it may cause the doping element to fail to achieve the improvement effect and fail to improve the thermal stability or electrochemical activity of the material.

[0067] Specifically, the porous coating layer in the present application contains Q1 elements, which can improve the conductivity of the positive electrode material. Secondly, the present application can improve the thermal stability and chemical stability of the material by coating with Q1 elements, thereby reducing the structural changes and thermal runaway risks of the material during the charging and discharging process. Furthermore, the use of Q1 elements for coating in the present application can improve the electrochemical activity of the positive electrode material, and increase the capacity and cycle life. Furthermore, the coating of Q1 elements in the present application can improve the interfacial interaction between the electrode and the electrolyte, reduce the interfacial impedance, and improve the overall performance of the battery. For example, tungsten (W) and molybdenum (Mo) in the Q1 element can form a conductive network in the porous coating layer, thereby reducing resistance; the Q1 element contains an appropriate amount of rare earth elements (Y) can improve the electrochemical activity of the positive electrode material, and increase the capacity and cycle life.

[0068] In some embodiments, the compound containing the Q2 element accounts for 0.01% to 0.20% of the mass of the intermediate material, for example, it can be 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.16%, 0.18% or 0.20%.

[0069] The present application selects the addition amount of the compound containing the Q2 element as above, and the Q2 element helps to maintain the mechanical stability of the second coating layer, thereby effectively balancing the conductivity and stability of the positive electrode material. If the addition amount is relatively high, it may cause phase separation and changes in the phase structure of the second coating layer, affecting the stability of the second coating layer. If the addition amount is relatively low, the structural stability / mechanical stability of the second coating layer may be poor.

[0070] Specifically, the present application contains Q2 elements in the second coating layer in the porous coating layer, which can improve the conductivity and mechanical strength of the positive electrode material. Among them, the Q2 element includes Mg, which can improve the conductivity of the material, promote the conduction of ions in the material, and thus improve the overall performance of the battery. It can also enhance the mechanical strength of the positive electrode material, reduce the volume change during the charge and discharge process, and extend the cycle life of the battery. The Q2 element includes Na, which helps to enhance the cycle performance of the positive electrode material and reduce the rate of capacity decay. Especially after multiple charge and discharge, it can maintain a high capacity. It can also enhance the interaction between the material and the electrolyte and improve the migration ability of ions, thereby improving battery performance. The Q2 element contains Sn, which has good conductivity and can improve the conductivity of the positive electrode material, while enhancing the electrochemical activity of the battery and increasing its specific capacity; it can also reduce the volume expansion of the material during the charge and discharge process and increase the mechanical stability of the material.

[0071] In some embodiments, during the mixing process of the lithium source, the cathode material precursor and the compound containing the M element, the stirring speed is 800 rpm to 1000 rpm and the time is 15 min to 40 min.

[0072] In some embodiments, the first calcination temperature is 550°C to 650°C, for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C.

[0073] In some embodiments, the first calcination time is 1.5 h to 3 h, for example, 1.5 h, 1.6 h, 1.8 h, 2.0 h, 2.2 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h or 3.0 h.

[0074] In some embodiments, the first calcination atmosphere is an oxygen-containing atmosphere, for example, the oxygen volume concentration in the oxygen-containing atmosphere is ≥ 99%.

[0075] In some embodiments, the heating rate of the first calcination is 1° C. / min to 3° C. / min.

[0076] In some embodiments, the material after the first calcination treatment is cooled and then stirred and mixed to obtain the core. Optionally, the mixing speed is 500 rpm to 600 rpm, and the mixing time is 5 min to 10 min.

[0077] In some embodiments, the second calcination comprises: sequentially performing a first stage calcination and a second stage calcination on the mixture.

[0078] Optionally, the temperature of the first stage calcination is 580°C to 620°C, for example, 580°C, 585°C, 590°C, 595°C, 600°C, 605°C, 610°C, 615°C or 620°C.

[0079] Optionally, the first stage calcination time is 5 h to 6 h, for example, it can be 5.0 h, 5.1 h, 5.2 h, 5.3 h, 5.4 h, 5.5 h, 5.6 h, 5.7 h, 5.8 h, 5.9 h or 6.0 h.

[0080] Optionally, the atmosphere of the first stage calcination is an oxygen-containing atmosphere, for example, the oxygen volume concentration in the oxygen-containing atmosphere is ≥99%.

[0081] Optionally, the heating rate of the first stage calcination is 1°C / min to 3°C / min.

[0082] In some embodiments, the temperature of the second stage calcination is 750°C to 800°C, for example, 750°C, 755°C, 760°C, 765°C, 770°C, 775°C, 780°C, 785°C, 790°C, 795°C or 800°C.

[0083] Optionally, the second stage calcination time is 11 h to 14 h, for example, it can be 11.0 h, 11.5 h, 12.0 h, 12.5 h, 13.0 h, 13.5 h or 14.0 h.

[0084] Optionally, the atmosphere of the second stage calcination is an oxygen-containing atmosphere, for example, the oxygen volume concentration in the oxygen-containing atmosphere is ≥99%.

[0085] Optionally, the heating rate of the second stage calcination is 1°C / min~5°C / min.

[0086] Optionally, the material after the second stage calcination is subjected to cooling treatment, crushing treatment, water washing treatment and drying treatment. Optionally, the rotation speed of the crushing treatment is 8000rpm~10000rpm. Optionally, the solid content of the treatment liquid containing the material after the second stage calcination in the water washing treatment is 50%~60%, and the water washing treatment time is 1min~3min. The temperature of the drying treatment is 100℃~200℃, and the time is 2h~4h.

[0087] In some embodiments, the temperature of the third calcination is 250°C to 300°C, for example, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C or 300°C.

[0088] The present application selects the temperatures of the first calcination, the first stage calcination, the second stage calcination, and the third calcination in the first calcination, the second calcination, and the third calcination as above, so that the formed first coating layer and the second coating layer have a porous structure, and have the advantages of increasing the specific surface area, improving the conductivity, promoting ion migration, and enhancing the cycle stability of the material. Among them, if the calcination temperature is relatively low, it may cause the coating layer structure to be uneven and the porosity to be insufficient, which in turn may cause the specific surface area and conductivity of the material to be insufficient, thereby affecting the overall performance of the battery; if the calcination temperature is relatively high, it may cause the coating layer to be too dense, the formation of pores is inhibited, and then the diffusion capacity of ions is affected, and the electrochemical performance and cycle life of the battery are reduced.

[0089] In some embodiments, the third calcination time is 4.5 h to 6 h, for example, 4.5 h, 4.6 h, 4.8 h, 5.0 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6.0 h.

[0090] In some embodiments, the atmosphere of the third calcination is an oxygen-containing atmosphere, for example, the volume concentration of oxygen in the oxygen-containing atmosphere is ≥ 99%.

[0091] In some embodiments, the heating rate of the third calcination is 1° C. / min to 2° C. / min.

[0092] In some embodiments, the material after the third calcination is cooled and sieved. Optionally, the mesh size of the sieve is 200-400 mesh.

[0093] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium nitrate.

[0094] In some embodiments, the cathode material precursor comprises a chemical formula of Ni x0 Co y0 Mn z0 (OH)2 material, wherein 0.8≤x0≤0.9, 0<y0<0.15, 0<z0<0.07, x0+y0+z0=1.

[0095] In some embodiments, the compound containing the element M may be at least one of an oxide, a carbonate, a chloride, a fluoride, and a hydroxide containing the element M. For example, when the element M is Ti, the compound containing the element M may be TiO2.

[0096] In some embodiments, the compound containing the Q1 element may be at least one of an oxide, a carbonate, a fluoride, and a hydroxide containing the Q1 element. For example, when the Q1 element is W, the compound containing the Q1 element may be WO3.

[0097] In some embodiments, the compound containing the Q2 element may be at least one of an oxide, a carbonate, a fluoride, and a hydroxide containing the Q2 element. For example, when the Q2 element is Mg, the compound containing the Q2 element may be MgO.

[0098] Exemplarily, a method for preparing the above-mentioned positive electrode material is provided, comprising the following steps:

[0099] Weigh the positive electrode material precursor and the lithium source according to a molar ratio of 1:1.02-1:1.05, and then weigh a compound containing the M element according to 0.01%-1% of the total mass of the positive electrode material precursor and the lithium source, mix them at a speed of 800rpm-1000rpm for 15min-40min in a high-speed mixer, and after mixing, perform a first calcination at 550℃-650℃ for 1.5h-3h in an oxygen-containing atmosphere, and after cooling down in an oxygen-containing atmosphere, mix and stir at 500rpm-600rpm for 5min-10min to obtain the core;

[0100] The inner core is mixed with a compound containing the Q1 element, wherein the compound containing the Q1 element accounts for 0.01% to 0.10% of the mass of the inner core, and the first stage of calcination is performed at 580° C. to 620° C. in an oxygen-containing atmosphere for 5 h to 6 h, and after cooling with the furnace, the mixture is mixed and stirred at 500 rpm to 600 rpm for 5 min to 10 min, and sieved through 200 mesh to 300 mesh; and then the second stage of calcination is performed at 750° C. to 800° C. in an oxygen-containing atmosphere for 11 h to 14 h, and after cooling, the mixture is crushed at 8000 rpm to 10000 rpm, washed with water, and dried to obtain an intermediate material having a first coating layer;

[0101] The intermediate material and the compound containing the Q2 element are mixed, and the compound containing the Q2 element accounts for 0.01% to 0.20% of the mass of the intermediate material. In an oxygen-containing atmosphere, the mixture is calcined for a third time at 250°C to 300°C for 4.5h to 6h to form a second coating layer. After cooling, the mixture is sieved with 200 mesh to 400 mesh to prepare the positive electrode material.

[0102] A third aspect of the present application provides a positive electrode plate, comprising at least one of the positive electrode material as described in the first aspect and the positive electrode material prepared by the preparation method as described in the second aspect.

[0103] The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, a conductive agent and a binder. The positive electrode active material comprises at least one of the positive electrode material or the positive electrode material prepared by the preparation method, and the conductive agent and the binder may be conductive agents and binders commonly used in the technical field.

[0104] A fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet as described in the third aspect.

[0105] The above-mentioned secondary battery may, for example, include the above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and diaphragm of the present application. The diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. During the charging and discharging process of the secondary battery, the active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, electrolyte and diaphragm, and the negative electrode sheet, electrolyte and diaphragm prepared by the preparation method commonly used in the technical field, or the negative electrode sheet, electrolyte and diaphragm commonly used in the art can be used. Optionally, the above-mentioned secondary battery includes a lithium-ion battery.

[0106] Furthermore, another embodiment of the present application also provides an electrical device, including the above-mentioned battery of the present application.

[0107] The above-mentioned electrical devices may include any equipment or devices that use secondary batteries as driving sources, such as mobile phones, laptop computers, electric vehicles, ships, satellites, energy storage devices, smart home appliances, etc., but are not limited thereto.

[0108] The embodiments of the present application will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are preferably referred to the guidance provided in the present application, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0109] In the following examples and comparative examples, the volume concentration of oxygen in the oxygen-containing atmosphere is 99%.

[0110] Example 1

[0111] Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.04 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH·H2O, and then according to Ni 0.83 Co 0.12 Mn 0.05Weigh TiO2 at 0.35% of the total mass of (OH)2 and LiOH·H2O, and 0.83 Co 0.12 Mn 0.05 0.10% of the total mass of (OH)2 and LiOH·H2O was weighed CrO, mixed at 850 rpm for 40 min by a high-speed mixer, and then heated to 560°C at a heating rate of 2.5°C / min in an oxygen-containing atmosphere for a first calcination for 3 h. After cooling, the mixture was mixed and stirred at 500 rpm for 10 min to obtain the core, which includes a chemical formula of LiNi 0.816 Co 0.11 Mn 0.04 Ti 0.03 Cr 0.004 O2 materials;

[0112] The core is mixed with WO3, wherein WO3 accounts for 0.05% of the core mass, and the temperature is raised to 620°C at 2.5°C / min in an oxygen-containing atmosphere for a first-stage calcination for 5 hours. After cooling with the furnace, the mixture is sieved through 325 meshes. Then, the second-stage calcination is carried out at 790°C in an oxygen-containing atmosphere for 11 hours. After cooling, the mixture is crushed at 9000 rpm, washed with water for 2 minutes, and dried at 150°C in sequence to obtain an intermediate material having a first coating layer. The material of the first coating layer includes a LiNi 0.815 Co 0.109 Mn 0.04 Ti 0.03 Cr 0.004 W 0.002 O2 materials;

[0113] The intermediate material and MgO are mixed, and MgO accounts for 0.20% of the mass of the intermediate material. In an oxygen-containing atmosphere, the mixture is calcined for a third time at 285°C for 5.5 hours to form a second coating layer. After cooling, the mixture is sieved through 325 mesh to prepare a positive electrode material with a median particle size Dv50 of 10 μm. The second coating layer includes a chemical formula of LiNi 0.8149 Co 0.1089 Mn 0.04 Ti 0.03 Cr 0.004 W 0.002 Mg 0.0002 O2 material, wherein the specific surface area of ​​the porous coating layer formed by the first coating layer and the second coating layer is 0.683m 2 / g.

[0114] Example 2

[0115] Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.02 0.86 Co 0.13 Mn 0.01(OH)2 and LiOH·H2O, and then according to Ni 0.86 Co 0.13 Mn 0.01 Weigh Al2O3 at 0.3% of the total mass of (OH)2 and LiOH·H2O, and 0.86 Co 0.13 Mn 0.01 0.10% of the total mass of (OH)2 and LiOH·H2O was weighed CrO, mixed at 850 rpm for 30 min by a high-speed mixer, and then heated to 570°C at a heating rate of 2.5°C / min in an oxygen-containing atmosphere for a first calcination for 2 h. After cooling, the mixture was mixed and stirred at 500 rpm for 5 min to obtain the core, which includes a chemical formula of LiNi 0.845 Co 0.115 Mn 0.01 Al 0.02 Cr 0.01 O2 materials;

[0116] The core is mixed with WO3, wherein WO3 accounts for 0.05% of the core mass, and the temperature is raised to 600°C at 2.5°C / min in an oxygen-containing atmosphere for a first-stage calcination for 5 hours. After cooling with the furnace, the mixture is sieved through 325 meshes. Then, the second-stage calcination is carried out at 760°C in an oxygen-containing atmosphere for 11 hours. After cooling, the mixture is crushed at 9000 rpm, washed with water for 2 minutes, and dried at 150°C in sequence to obtain an intermediate material having a first coating layer. The material of the first coating layer includes a LiNi 0.844 Co 0.114 Mn 0.01 Al 0.02 Cr 0.01 W 0.002 O2 materials;

[0117] The intermediate material and MgO are mixed, and MgO accounts for 0.20% of the mass of the intermediate material. In an oxygen-containing atmosphere, the mixture is calcined for a third time at 285°C for 5.5 hours to form a second coating layer. After cooling, the mixture is sieved through 325 mesh to prepare a positive electrode material with a median particle size Dv50 of 10.2 μm. The second coating layer includes a chemical formula of LiNi 0.8437 Co 0.114 Mn 0.01 Al 0.02 Cr 0.01 W 0.002 Mg 0.0003 O2 material, wherein the specific surface area of ​​the porous coating layer formed by the first coating layer and the second coating layer is 0.654m 2 / g.

[0118] Example 3

[0119] Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.05 0.84 Co 0.11 Mn 0.05 (OH)2 and LiOH·H2O, and then according to Ni 0.84 Co 0.11 Mn 0.05 0.3% of the total mass of (OH)2 and LiOH·H2O was weighed Al2O3, mixed at 800 rpm for 30 min by a high-speed mixer, and then heated to 600°C at a heating rate of 2°C / min in an oxygen-containing atmosphere for a first calcination for 2 h. After cooling, the mixture was mixed and stirred at 520 rpm for 10 min to obtain the core, which includes a chemical formula of LiNi 0.835 Co 0.108 Mn 0.037 Al 0.02 O2 materials;

[0120] The core is mixed with Mo2O3, wherein Mo2O3 accounts for 0.03% of the core mass, and the temperature is raised to 580°C at 2.5°C / min in an oxygen-containing atmosphere for a first-stage calcination for 5 hours. After cooling with the furnace, the mixture is sieved through 325 meshes. Then, the core is calcined at 770°C for 11 hours in an oxygen-containing atmosphere. After cooling, the mixture is crushed at 9000 rpm, washed with water for 2 minutes, and dried at 150°C in sequence to obtain an intermediate material having a first coating layer. The material of the first coating layer includes a LiNi 0.8346 Co 0.10 7Mn 0.037 Al 0.02 Mo 0.0014 O2 materials;

[0121] The intermediate material and NaOH were mixed, with NaOH accounting for 0.15% of the mass of the intermediate material. The mixture was calcined for a third time at 290°C for 6 hours in an oxygen-containing atmosphere to form a second coating layer. After cooling, the mixture was sieved through 325 mesh to prepare a positive electrode material with a median particle size Dv50 of 10.1 μm. The second coating layer included a LiNi 0.8344 Co 0.107 Mn 0.037 Al 0.02 Mo 0.0014 Na 0.0002 O2 material, wherein the specific surface area of ​​the porous coating layer formed by the first coating layer and the second coating layer is 0.657m 2 / g.

[0122] Example 4

[0123] Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.04 0.85 Co 0.10 Mn0.05 (OH)2 and LiOH·H2O, and then according to Ni 0.85 Co 0.10 Mn 0.05 0.3% of the total mass of (OH)2 and LiOH·H2O was weighed Al2O3, mixed at 850 rpm for 40 min by a high speed mixer, and then heated to 575°C at a heating rate of 2.5°C / min in an oxygen-containing atmosphere for a first calcination for 2.5 h. After cooling, the mixture was mixed and stirred at 530 rpm for 5 min to obtain the core, which includes a chemical formula of LiNi 0.847 Co 0.084 Mn 0.049 Al 0.02 O2 materials;

[0124] The core is mixed with Y2O3, wherein Y2O3 accounts for 0.05% of the core mass, and the temperature is raised to 620°C at 2.5°C / min in an oxygen-containing atmosphere for a first-stage calcination for 5 hours. After cooling with the furnace, the mixture is sieved through 325 meshes. Then, the second-stage calcination is carried out at 789°C in an oxygen-containing atmosphere for 11 hours. After cooling, the mixture is crushed at 9000 rpm, washed with water for 2 minutes, and dried at 150°C in sequence to obtain an intermediate material having a first coating layer. The material of the first coating layer includes a chemical formula of LiNi 0.846 Co 0.0835 Mn 0.0486 Al 0.02 Y 0.0019 O2 materials;

[0125] The intermediate material, NaOH and MgO are mixed, with NaOH accounting for 0.05% of the intermediate material and MgO accounting for 0.10% of the intermediate material. The mixture is calcined for a third time at 290°C for 6 hours in an oxygen-containing atmosphere to form a second coating layer. After cooling, the mixture is sieved through 325 mesh to obtain the following: Figure 1 The positive electrode material shown has a median particle size Dv50 of 10.1 μm, and the second coating layer includes a chemical formula of LiNi 0.8459 Co 0.0834 Mn 0.0485 Al 0.02 Y 0.0019 Na 0.0001 Mg 0.0002 O2 material, wherein the specific surface area of ​​the porous coating layer formed by the first coating layer and the second coating layer is 0.685m 2 / g.

[0126] Example 5

[0127] Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.03 0.80 Co 0.14 Mn0.06 (OH)2 and LiOH·H2O, and then according to Ni 0.80 Co 0.14 Mn 0.06 Weigh V2O5 at 0.01% of the total mass of (OH)2 and LiOH·H2O, and 0.80 Co 0.14 Mn 0.06 TiO2 is weighed at 0.02% of the total mass of (OH)2 and LiOH·H2O, mixed at 850 rpm for 40 min by a high-speed mixer, and then heated to 650°C at a heating rate of 2.5°C / min in an oxygen-containing atmosphere for a first calcination for 1.5 h. After cooling, the mixture is mixed and stirred at 550 rpm for 5 min to obtain the core, which includes a chemical formula of LiNi 0.80 Co 0.125 Mn 0.0 5V 0.01 Ti 0.015 O2 materials;

[0128] The core is mixed with ZrO2, ZrO2 accounts for 0.08% of the core mass, and the temperature is raised to 610°C at 2.5°C / min in an oxygen-containing atmosphere for a first-stage calcination for 6 hours. After cooling with the furnace, the mixture is sieved through 325 meshes. Then, the second-stage calcination is carried out at 800°C in an oxygen-containing atmosphere for 12 hours. After cooling, the mixture is crushed at 9000 rpm, washed with water for 2 minutes, and dried at 150°C in sequence to obtain an intermediate material having a first coating layer. The material of the first coating layer includes a chemical formula of LiNi 0.80 Co 0.124 Mn 0.0493 V 0.01 Ti 0.015 Zr 0.0017 O2 materials;

[0129] The intermediate material and SnO2 are mixed, SnO2 accounts for 0.05% of the mass of the intermediate material, and the mixture is calcined for a third time at 250°C for 6 hours in an oxygen-containing atmosphere to form a second coating layer. After cooling, the mixture is sieved through 325 mesh to prepare a positive electrode material with a median particle size Dv50 of 10.2 μm. The second coating layer includes a chemical formula of LiNi 0.80 Co 0.124 Mn 0.049 V 0.01 Ti 0.015 Zr 0.0017 Sn 0.0003 O2 material, wherein the specific surface area of ​​the porous coating layer formed by the first coating layer and the second coating layer is 0.64m 2 / g.

[0130] Example 6

[0131] The positive electrode material was prepared according to the method of Example 4, except that the added amount of Y2O3 accounted for 0.005% of the core mass.

[0132] Example 7

[0133] The positive electrode material was prepared according to the method of Example 4, the only difference being that the amount of Y2O3 added accounted for 0.5% of the core mass.

[0134] Example 8

[0135] The positive electrode material was prepared according to the method of Example 4, with the only difference being that NaOH accounted for 0.18% of the mass of the intermediate material and MgO accounted for 0.12% of the mass of the intermediate material.

[0136] Example 9

[0137] The positive electrode material was prepared according to the method of Example 4, with the only difference being that NaOH accounted for 0.003% of the mass of the intermediate material and MgO accounted for 0.002% of the mass of the intermediate material.

[0138] Example 10

[0139] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the first stage calcination was 550°C.

[0140] Embodiment 11

[0141] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the first stage calcination was 650°C.

[0142] Example 12

[0143] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the second stage calcination was 700°C.

[0144] Embodiment 13

[0145] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the second stage calcination was 850°C.

[0146] Embodiment 14

[0147] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the third calcination was 200°C.

[0148] Embodiment 15

[0149] The positive electrode material was prepared according to the method of Example 4, except that the temperature of the third calcination was 350°C.

[0150] Comparative Example 1

[0151] The positive electrode material is prepared according to the method of Example 4, except that the first coating layer is not formed, and the second coating layer is directly formed on the surface of the core. The preparation method includes:

[0152] (1) Weigh the positive electrode material precursor Ni according to the molar ratio of 1:1.04 0.85 Co 0.10 Mn 0.05 (OH)2 and LiOH·H2O, and then according to Ni 0.85 Co 0.10 Mn 0.05 0.3% of the total mass of (OH)2 and LiOH·H2O was weighed Al2O3, mixed at 850 rpm for 40 min in a high-speed mixer, and then heated to 575°C at a heating rate of 2.5°C / min in an oxygen-containing atmosphere for a first calcination for 2.5 h. After cooling, the mixture was mixed and stirred at 530 rpm for 5 min to obtain the core;

[0153] The core, NaOH and MgO were mixed, with NaOH accounting for 0.05% of the core mass and MgO accounting for 0.10% of the core mass. The mixture was calcined for a third time at 290°C for 6 hours in an oxygen-containing atmosphere to form a second coating layer on the surface of the core. After cooling, the mixture was sieved through 325 mesh to prepare the following: Figure 2 The positive electrode material shown.

[0154] Comparative Example 2

[0155] The positive electrode material is prepared according to the method of Example 4, the only difference being that the intermediate material is directly used as the positive electrode material, that is, the second coating layer is not formed.

[0156] Comparative Example 3

[0157] The positive electrode material was prepared according to the method of Example 4, the only difference being that the inner core was directly used as the positive electrode material, and the first coating layer and the second coating layer were not formed.

[0158] The components of the positive electrode materials prepared in each embodiment and each comparative example were measured using an ICP-AES (inductively coupled plasma atomic emission spectrometer).

[0159] The specific surface area of ​​the porous coating layer in the positive electrode materials prepared in each embodiment and each comparative example is measured using a specific surface area meter.

[0160] The residual lithium content of the positive electrode materials prepared in each embodiment and each comparative example is tested by the following method:

[0161] Weigh 5 g of the sample to be tested into a beaker, then add 100 mL of distilled water to the beaker, stir for 30 minutes, and let stand for 10 minutes;

[0162] After filtration, the filtrate was collected in a titration cup and the residual lithium content was tested using a potentiometric titrator. The test results are shown in Table 1.

[0163] Battery assembly and electrochemical performance testing

[0164] The positive electrode materials prepared in each embodiment and comparative example were made into positive electrode sheets, and the positive electrode sheets were prepared according to the mass ratio of positive electrode material: conductive agent super carbon black: PVDF (polyvinylidene fluoride) = 96.5:2:1.5. The above positive electrode sheets were assembled into button batteries of model LR2032, and then the cycle performance was tested.

[0165] The cycle performance test conditions are: room temperature (25°C), voltage 2.8V~4.25V, and battery cycle performance at 0.33C. The test results are shown in Table 1. The relationship between the cycle number and capacity retention rate of Example 4 and Comparative Example 1 is shown in Figure 3 shown.

[0166] Table 1

[0167]

[0168] From the above table we can see that:

[0169] (1) Compared with Examples 6-7, it can be seen that the present application can effectively reduce the residual alkali and improve the cycle performance by controlling the coating amount of the Q1 element in the first coating layer.

[0170] (2) Compared with Examples 8-9, it can be seen that the present application effectively avoids the problem of high residual alkali by controlling the coating amount of the Q2 element in the second coating layer, thereby avoiding affecting the capacity performance of the positive electrode material.

[0171] (3) Compared with Examples 10-13, it can be seen that the present application forms a first coating layer with a shallow surface coating of Q1 element by controlling the temperature of the second calcination, which has a stable structure and can prevent the coating element from blocking the lithium ion channel, thereby effectively ensuring the capacity of the material.

[0172] (4) By comparing Example 4 with Examples 14-15, it can be seen that the present application forms a second coating layer with uniform dot-shaped coating by controlling the temperature of the third calcination, and the coating is stable, which can effectively prevent the structure from falling off.

[0173] (5) Example 4 is compared with Comparative Examples 1-3, and combined with Figure 1 , Figure 2 and Figure 3It can be seen that the positive electrode material of the present application forms a porous coating layer by coating N elements and P elements, which can effectively reduce the residual lithium on the surface and reduce the release of active lithium during the water washing process. Among them, the first coating layer contains N elements, which can also promote the deintercalation of lithium ions and improve the cycle performance; the second coating layer contains P elements, which can avoid the structural changes caused by the volume change of the positive electrode material during the deintercalation of lithium ions, so as to enhance the structural stability of the positive electrode material. The first coating layer and the second coating layer cooperate to improve the structural stability and cycle performance of the positive electrode material.

[0174] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0175] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the application. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a core, and a porous coating layer coated on at least a portion of the surface of the core, wherein the porous coating layer comprises a first coating layer and a second coating layer stacked in sequence in a direction away from the surface of the core; The core comprises a chemical formula of LiNi x Co y Mn z M a O2 materials, wherein 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1; The first coating layer comprises a chemical formula of LiNi x1 Co y1 Mn z1 M a1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1; The second coating layer comprises a chemical formula of LiNi x2 Co y2 Mn z2 M a2 Q1 b2 Q2 c2 O2, Q2 element includes at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1; The M element includes at least one of Al, Ti, V and Cr.

2. The positive electrode material according to claim 1, characterized in that The molar ratio of the Q1 element to the Q2 element in the porous coating layer is 3.5:1 to 4.5:

1.

3. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The mass content of Q1 element in the positive electrode material is 0.001%~0.1%; (2) The mass content of Q2 element in the positive electrode material is 0.001%~0.2%; (3) The mass content of the M element in the positive electrode material is 0.001%~0.5%.

4. The positive electrode material according to claim 1, characterized in that The specific surface area of ​​the porous coating layer is 0.3 m 2 / g~0.7m 2 / g.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The median particle size Dv50 of the positive electrode material is 9 μm to 12 μm.

6. A method for preparing a positive electrode material, characterized in that: The preparation method of the positive electrode material comprises: The lithium source, the cathode material precursor and the compound containing the M element are mixed, and after the first calcination, a LiNi x Co y Mn z M a The inner core of the material of O2, wherein 0.8≤x≤0.9, 0<y<0.15, 0<z<0.07, 0<a≤0.04, x+y+z+a=1; The core is mixed with a compound containing the Q1 element to obtain a mixture, and subjected to a second calcination to form a first coating layer on the surface of the core to obtain an intermediate material; the first coating layer contains a chemical formula of LiNi x1 Co y1 Mn z1 M a1 Q1 b1 O2 material, wherein the Q1 element includes at least one of Zr, Y, Mo and W, 0.8≤x1≤0.9, 0<y1<0.15, 0<z1<0.07, 0<a1≤0.04, 0<b1≤0.002, x1+y1+z1+a1+b1=1; The intermediate material is mixed with a compound containing the Q2 element, and subjected to a third calcination to form a second coating layer on the surface of the intermediate material to obtain the positive electrode material, wherein the second coating layer contains a chemical formula of LiNi x2 Co y2 Mn z2 M a2 Q1 b2 Q2 c2 O2, Q2 element includes at least one of Mg, Na and Sn, 0.8≤x2≤0.9, 0<y2<0.15, 0<z2<0.07, 0<a2≤0.04, 0<b2≤0.002, 0<c2≤0.0005, x2+y2+z2+a2+b2+c2=1; The M element includes at least one of Al, Ti, V and Cr.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The preparation method of the positive electrode material satisfies at least one of the following conditions: (1) The molar ratio of the positive electrode material precursor to the lithium source is 1:1.02 to 1:1.05; (2) The compound containing the M element accounts for 0.01% to 1.00% of the total mass of the lithium source and the positive electrode material precursor; (3) The compound containing the Q1 element accounts for 0.01% to 0.10% of the mass of the core; (4) The compound containing the Q2 element accounts for 0.01% to 0.20% of the mass of the intermediate material.

8. The method for preparing the positive electrode material according to claim 6 or 7, characterized in that: The method for preparing the positive electrode material also satisfies at least one of the following conditions: (1) The first calcination temperature is 550°C to 650°C, the time is 1.5h to 3h, and the atmosphere is an oxygen-containing atmosphere; (2) the second calcination comprises: sequentially performing a first stage calcination and a second stage calcination on the mixture; Optionally, the temperature of the first stage calcination is 580°C to 620°C, the time is 5h to 6h, and the atmosphere is an oxygen-containing atmosphere; Optionally, the temperature of the second stage calcination is 750°C to 800°C, the time is 11h to 14h, and the atmosphere is an oxygen-containing atmosphere; (3) The temperature of the third calcination is 250° C. to 300° C., the time is 4.5 h to 6 h, and the atmosphere is an oxygen-containing atmosphere.

9. A positive electrode sheet, characterized in that: The invention comprises at least one of the positive electrode materials described in any one of claims 1 to 5 and the positive electrode materials prepared by the preparation method described in any one of claims 6 to 8.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.